PERBANDINGAN AKTIVITAS DAN HASIL BELAJAR KIMIA SISWA SMAN 2 ARGAMAKMUR PADA PEMBELAJARAN MENGGUNAKAN TEAM ASSISTED INDIVIDUALIZATION DAN GROUP INVESTIGATION BERBASIS KURIKULUM 2013 - Ria Kemala Dewi; Sumpono Sumpono; Salastri Rohiat (ALOTROP, 2018)
This research was aimed to know  the differences between the student’s chemical learning activities and achievement by using a models called Team Assisted Individualization and Group Investigation based on Curriculum 2013. The samples in this research is class X MIA 3 (Team Assisted Individualization) and X MIA 6 (Group Investigation). The result of this research is learning activities and achievement and than the analysis used are the score and percentage of mean, normality tests, homogeneity tests, hypothesis tests. The observation result of student’s learning activities in the 1 and 2 of experimental class was 78.79% and 68,18%. The mean score of student’s achievement for experimental class 1 and 2 was 80,56 and 75,31. The result of t test obtained tcount > ttable, 10,6 > 1,0 for learning activities and 3,36 > 2,30 for achievement. It means there was a significant differences between the student’s chemical learning activities and achievement by using both models of learning.